The correlation between Rood and Shehab’s radiographic features and the incidence of inferior alveolar nerve paraesthesia following odontectomy of lower third molars - David Buntoro Kamadjaja; Djodi Asmara; Gita Khairana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Odontectomy of lower third molar has a potential risk for inferior alveolar nerve impairment. Paresthesia of inferior alveolar nerve has often been associated with close relationship between the apex of lower third molar and mandibular canal. Rood and Shehab’s category has been commonly used for radiological prediction of inferior alveolar nerve injury following third molar surgery. Purpose: This study aimed to determine whether there was correlation between Rood and Shehab’s radiographic features and the incidence of inferior alveolar nerve paraesthesia following odontectomy of lower third molar. Method: This was a retrospective cross-sectional study, using data obtained from the dental record of patients who had undergone odontectomy of lower third molars in Dental hospital of Universitas Airlangga during 2 years period. Samples were cases that, from presurgical radiograph, showed close relationship between lower third molar roots and mandibular canal. The case and non-case groups were assigned based on the presence of paraesthesia and non-paraesthesia of inferior alveolar nerves, respectively. Based on Rood and Shehab’s category, the samples collected were then classified into two groups which were those whose relationship matched and did not match with the category, respectively. Data were analyzed using Chi-square correlation test. Result: Of 975 odontectomy cases included in this study, 80 cases were taken as study samples consisting of 15 and 65 cases assigned, respectively, as case and non-case. The 32 cases matched with the criteria of Rood and Shehab's category while the remainder of 48 cases did not. Of 32 cases which met the criteria of Rood and Shehab’s relationship, only 5 cases showed paraesthesia, whereas out of 48 cases which did not met the criteria 10 cases showed paraesthesia. Statistical analysis showed significance value of 0.770 (p>0.05) indicating that there was no significant correlation between relations of third molar root and mandibular canal, based on Rood and Shehab’s category, and the incidence of inferior alveolar nerve paraesthesia. Conclusion: There was no correlation between Rood and Shehab’s radiographic features and the incidence of paraesthesia of inferior alveolar nerve following odontectomy of lower third molars.